Eksplorasi Daya Tarik Wisata Urban Heritage Dan Modern Leisure: Studi Kasus Kota Lama Surabaya Dan Blyss Cafe Batu Malang - Zaskiya Bella Usnul Qotimah; Salsa Aulia Ayu Yasmine; Mohammad Insan Romadhan (CV. ITTC INDONESIA, 2025)
Tourism in East Java shows an increasingly dynamic trend, with the emergence of a combination of heritage tourism attractions and modern leisure concepts. The Old City of Surabaya as an urban heritage area holds strong historical potential, while Blyss Cafe in Batu, Malang, represents a leisure tourism lifestyle that is popular with the younger generation. This study aims to explore and compare the attractions of the two locations in the context of destination development and East Java tourism branding strategies. The research method used is a descriptive qualitative approach, with data collection techniques through direct observation, in-depth interviews with managers and visitors, and analysis of visual documentation and related literature. The research findings show that the Old City of Surabaya has strengths in historical value and cultural narratives, while Blyss Cafe excels in presenting an aesthetic atmosphere, comfort, and leisure experiences that attract millennial tourists. Although different in character, both play an important role in shaping a diverse and inclusive destination image. In conclusion, the integration of heritage tourism and modern leisure can be an effective destination branding strategy, by targeting a wider tourist segment while enriching the East Java tourism portfolio.